Circadian Modulation of Dopamine Levels and Dopaminergic Neuron Development Contributes to Attention Deficiency and Hyperactive Behavior - Huang, Jian; Zhong, Zhaomin; Wang, Mingyong; Chen, Xifeng; Tan, Yicheng; Zhang, Shuqing; He, Wei; He, Xiong; Huang, Guodong; Lu, Haiping; Wu, Ping; Che, Yi; et al. (The Journal of neuroscience, 2015)
Attention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent psychiatric disorders in children and adults. While ADHD patients often display circadian abnormalities, the underlying mechanisms are unclear. Here we found that the zebrafish mutant for the circadian gene period1b ( per1b ) displays hyperactive, impulsive-like, and attention deficit-like behaviors and low levels of dopamine, reminiscent of human ADHD patients. We found that the circadian clock directly regulates dopamine-related genes monoamine oxidase and dopamine β hydroxylase , and acts via genes important for the development or maintenance of dopaminergic neurons to regulate their number and organization in the ventral diencephalic posterior tuberculum. We then found that Per1 knock-out mice also display ADHD-like symptoms and reduced levels of dopamine, thereby showing highly conserved roles of the circadian clock in ADHD. Our studies demonstrate that disruption of a circadian clock gene elicits ADHD-like syndrome. The circadian model for attention deficiency and hyperactive behavior sheds light on ADHD pathogenesis and opens avenues for exploring novel targets for diagnosis and therapy for this common psychiatric disorder.